Analisis Bauran Informasi Sebagai Strategi Pemasaran Informasi Di Perpustakaan Universitas Islam Riau: Pemasaran informasi perpustakaan - Hurriya Ulfa (UIN Mataram, 2024)
Nowadays, libraries face many problems. Due to the development of information technology that is growing rapidly, so that this phenomenon not only makes it easier for humans to get information but also becomes a threat to the extinction of libraries. Therefore, every library must have a strategy to maintain the function of the library as an information provider institution by the public. One way is to apply the 4P marketing mix (Price, Product, Place and Promotion) such as the Riau Islamic University library which has implemented the concept.The purpose of this study was to analyze the information mix as an information marketing strategy at the Riau Islamic University library. The method used in this research is a qualitative method with a case study approach.Data was collected through interviews, observations, and document analysis.The participants of this research consisted of librarians and users who were selected purposively.The results showed that the information mix at the Riau Islamic University library included four main components, namely information promotion, information distribution, information content, and user interaction.Information promotion involves the use of social media, websites, and electronic newsletters to disseminate information about library services and resources.